CD69+CD103+CD8+ tissue-resident memory T cells possess stronger anti-tumor activity and predict better prognosis in colorectal cancer - Zi-Xin Wu; Tian-Tian Da; Chuan Huang; Xiao-Qing Wang; Liang Li; Zhi-Bin Zhao; Ting-Ting Yin; Hai-Qing Ma; Zhe-Xiong Lian; Jie Long; Fei Wang; Jie Cao (Cell Communication and Signaling)
Abstract Background Colorectal cancer (CRC) is one of the most prevalent cancers worldwide. Despite advancements in therapeutic methodologies, it still causes a high rate of patient mortality. CD8+ tissue-resident memory T (TRM) cells are strategically positioned to mediate effective anti-tumor responses. However, the characteristic surface molecules and functions of CD8+ TRM cells exhibit significant heterogeneity. Methods The roles and anti-tumor biological functions of different CD8+ TRM subsets in CRC were determined by clinical CRC samples, bioinformatics analysis, and in vitro experiments including co-culture experiments and transwell migration assays. The signaling pathways that synergistically regulate the differentiation of CD8+ TRM cells were identified by in vitro CD8+ T cell activation and inhibition assays, and the functioning transcription factors were predicted using the UCSC and JASPAR databases. Results We found that different CD8+ TRM subsets existed in CRC tumor tissues, which were identified as CD69−CD103−CD8+ TRM, CD69+CD103−CD8+ TRM (SP CD8+ TRM), and CD69+CD103+CD8+ TRM (DP CD8+ TRM) subsets. Compared with SP CD8+ TRM cells, increased infiltration of DP CD8+ TRM cells predicted better prognosis and played a protective role mainly in tumor invasion and lymph node metastasis of CRC. DP CD8+ TRM cells expressed higher levels of effector molecules and exerted stronger anti-tumor effects in a FAS/FASL pathway-dependent manner. Additionally, DP CD8+ TRM cells secreted higher levels of CXCL13 and recruited B cells into tumor tissues through the CXCL13/CXCR5 signaling axis to form tertiary lymphoid structures, participating in anti-tumor immune responses. Notch and TGF-β signaling pathways synergistically regulate the differentiation of DP CD8+ TRM cells. Conclusions We clarified the roles and mechanisms of different CD8+ TRM subsets in CRC and identified that DP CD8+ TRM cells exert stronger anti-tumor effects and predict better prognosis, which provides ideas for developing new clinically available therapeutic targets.